The roles of multimodal pedagogic effects and classroom environment in willingness to communicate in English. (June 2019) - Peng, Jian-E
Abstract: Multimodality has become a prominent concept in communication and language education research, and pedagogic discourse in second language (L2) classrooms is fundamentally multimodal. While research on willingness to communicate (WTC) has been thriving, little is known about how L2 WTC is related to multimodal classroom pedagogies. This article presents findings from the first large-scale survey study of its kind on EFL students' perceptions of multimodal pedagogies, and the interrelationships between multimodal pedagogic effects, classroom environment, and WTC in English. Data were collected from 2058 Chinese EFL university students and analyzed using frequency analysis and structural equation modeling. The results showed that the use of audio/video and teachers' voices/facial expressions were perceived by the participants as the most satisfactory, whereas the visual design of PowerPoint slides was the least satisfactory. Effective use of audio/video significantly predicted classroom environment and WTC, while teachers' voices/facial expressions contributed to classroom environment, and teachers' gestures and spatial positions predicted WTC. In addition, classroom environment was the strongest predictor of WTC. The findings have immediate implications for L2 teaching and will enable L2 teachers to exploit the potential of multimodal pedagogies to promote students' WTC and to benefit their learning.